2020
DOI: 10.1073/pnas.1919470117
|View full text |Cite
|
Sign up to set email alerts
|

The formation of the thumb requires direct modulation of Gli3 transcription by Hoxa13

Abstract: In the tetrapod limb, the digits (fingers or toes) are the elements most subject to morphological diversification in response to functional adaptations. However, despite their functional importance, the mechanisms controlling digit morphology remain poorly understood. Here we have focused on understanding the special morphology of the thumb (digit 1), the acquisition of which was an important adaptation of the human hand. To this end, we have studied the limbs of the Hoxa13 mouse mutant that specifically fail … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…3), after which shh expression becomes undetectable. Expression of gli3, which, in turn, determines anterior limb identity (30,31,(33)(34)(35)(36), is detected at low intensity from stages 42 to 44 and increases strongly throughout the fin afterward at stage 45 ( Fig. 3).…”
Section: Characterization Of the Lungfish Zpamentioning
confidence: 99%
“…3), after which shh expression becomes undetectable. Expression of gli3, which, in turn, determines anterior limb identity (30,31,(33)(34)(35)(36), is detected at low intensity from stages 42 to 44 and increases strongly throughout the fin afterward at stage 45 ( Fig. 3).…”
Section: Characterization Of the Lungfish Zpamentioning
confidence: 99%
“…However, whereas our lineage analysis clearly demonstrates that the morphological digit 1 rescued in the Shh cre/-;Shh-SmoM2 arises from anterior non-ZPA limb cells, we found that the single dysmorphic digit present in the Shh null mutant (Shh cre/-) is actually descended from posterior ZPA (LacZ+) d4/d5 progenitor cells (Figure 4c, extended data Figure 3a). Consistent with digit 1 identity, Hoxa13, which is critical for digit 1 specification 27,29,40 , and is absent or greatly reduced in Shh Cre/-(0/4, Figure 4d (Figure 4e). Yet, a relay mechanism is incompatible with Shh acting either as a traditional morphogen or by temporal integration, as supported by gain-of-function chick studies showing graded effects 1-3 .…”
Section: Shh Is Required Indirectly To Specify Digit 1 (Thumb)mentioning
confidence: 69%
“…The balance of antagonistic 5 0 Hoxd and Gli3 levels determines the dominance of limb axis polarity The 5 0 Hoxd genes have been shown to antagonize Gli3 function in several contexts during early and late phases of limb development. [9][10][11][12][13] We previously found that each of the three 5 0 Hoxd members can interact directly with Gli3, 9 and co-expression studies indicate that the stoichiometric balance of this protein interaction dictates the net effect on 5 0 Hoxd-and Gli3R-regulated target gene expression, 9,13 rather than strictly by transcriptional regulation (see Figure S3 in Huang et al, 10 and see Bastida et al 25 ). The functional level of Gli3R controls limb A-P polarity, and we hypothesized that 5 0 Hoxd proteins may act in concert in different limb domains to modulate Gli3 activity levels and regulate limb axis polarity.…”
Section: Resultsmentioning
confidence: 96%